A Thousand Words Are Worth a Picture: Snapshots of Printed-Word Processing in an Event-Related Potential Megastudy. (December 2015) - Dufau, Stéphane; Grainger, Jonathan; Midgley, Katherine J.; Holcomb, Phillip J.
In the experiment reported here, approximately 1, 000 words were presented to 75 participants in a go/no-go lexical decision task while event-related potentials (ERPs) were recorded. Partial correlations were computed for variables selected to reflect orthographic, lexical, and semantic processing, as well as for a novel measure of the visual complexity of written words. Correlations were based on the item-level ERPs at each electrode site and time slice while a false-discovery-rate correction was applied. Early effects of visual complexity were seen around 50 ms after word onset, followed by the earliest sustained orthographic effects around 100 to 150 ms, with the bulk of orthographic and lexical influences arising after 200 ms. Effects of a semantic variable (concreteness) emerged later, at around 300 ms. The overall time course of these ERP effects is in line with hierarchical, cascaded, interactive accounts of word recognition, in which fast feed-forward influences are consolidated by top-down feedback via recurrent processing loops.